Basal Cell Carcinoma - Mustofa, Ali; Nur Sholikah, Tri Rosalia; Niari, Tapi Singgar; Rahmawati, Yuli Wahyu (Universitas Muhammadiyah Semarang, 2022)
Background: Basal Cell Carcinoma (BCC) is a malignant neoplasm of non-keratinized cells in the basal layer of the epidermis, which is locally invasive, aggressive, destructive, and rarely metastasizes. BCC more commonly occurs in the elderly. Exposure to ultraviolet (UV) rays is the main risk factor for BCC, so predilection is areas of the body that are exposed to UV rays, especially the face, ears, and neck.Case presentation: The following is a case report of a 65-year-old female patient who works as a farmer. The patient was diagnosed with basal cell carcinoma (BCC) with complaints of black nodules on the face, itching, and bleeding easily. With Dermatological status obtained. The lesion ad regio Fascialis Dextra shows a solitary hyperpigmented nodule, nummular in size, well-circumscribed, and unilateral.Conclusion:Basal cell carcinoma is a malignant skin tumor originating from non-keratinizing cells in the basal layer of the epidermis.